2010
DOI: 10.5114/wiitm.2010.18825
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic surgery cholecystectomy in children – preliminary experience

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…It requires complete ambidexterity and adaptation to the new type of instruments’ navigation [617]. Non-intuitive preparation in the narrow space with altered visualization of the operative field and the need for strict cooperation with the assistant holding the laparoscopic camera forces a new learning curve for both the surgeon and the entire surgical team [617]. The findings of our study lead to similar conclusions.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It requires complete ambidexterity and adaptation to the new type of instruments’ navigation [617]. Non-intuitive preparation in the narrow space with altered visualization of the operative field and the need for strict cooperation with the assistant holding the laparoscopic camera forces a new learning curve for both the surgeon and the entire surgical team [617]. The findings of our study lead to similar conclusions.…”
Section: Discussionsupporting
confidence: 72%
“…Crossing of these instruments is often necessary, which necessitates changing of previously learned “laparoscopic” behaviours. It requires complete ambidexterity and adaptation to the new type of instruments’ navigation [617]. Non-intuitive preparation in the narrow space with altered visualization of the operative field and the need for strict cooperation with the assistant holding the laparoscopic camera forces a new learning curve for both the surgeon and the entire surgical team [617].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of these 2 patients required any thoracic drainage as the control bed-side chest X-ray showed no pneumothorax at the end of the procedure. Only one study has reported such a complication so far [33], although it seems it might be more frequent than reported. When we planned the procedure with the use of a transabdominal suspension suture we based it on the experience of Endo et al ., who placed such a suture in the intersection of the 7 th intercostal space and midclavicular line with no pneumothorax in his group of 132 patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our approach was to use standard equipment (laparoscopic cameras, typical surgical tools), and not interfere with medical procedures. We also planned to use our approach for both laparoscopic and single incision laparoscopic surgery [4, 5]. …”
Section: Introductionmentioning
confidence: 99%